The risk analysis of workers at height at construction companies in Kepulauan Riau - Meidia Wahyuni; Herniwanti Herniwanti; Ahmad Satria Efendi; Endang Purnawati Rahayu; Asril Asril (Universitas 'Aisyiyah Yogyakarta, 2022)
Construction work cannot be separated from working at heights that have a high risk of danger and accidents. The purpose of this study was to analyze the risk of work at height at a construction company in Kepulauan Riau. The method used descriptive qualitative with sampling using the snowball technique. The results of hazard identification using the HIRARC method were obtained from 2 activities with 22 potential hazards with a very high risk level of 13, priority 1 of 6 and substantial of 3. The control hierarchy that had been carried out by the company was engineering control, administrative and use of Personal Protective Equipment.